The effects of thermal procedure on transformation temperature, crystal structure and microstructure of Cu-Al-Co shape memory alloy - Aydogdu, Y.; Kok, M.; Dagdelen, F.; Aydogdu, A.; Turabi, A. S.; Karaca, H. E. (Iop Publishing Ltd, 2016)
The purpose of this study is to investigate the effects of different thermal procedures of the Cu-Al-Co shape memory alloy on its crystal structure, transformation temperature and microstructure. The alloys were subjected to a heat treatment and then cooling was applied at four different conditions. After the thermal process, XRD, DSC, optical microscopy and micro-hardness measurements were carried out. The experimental studies showed that crystal structure, microstructure and transformation temperature of Cu-Al-Co alloy were changed from the cooling conditions.
9th International Conference on Magnetic and Superconducting Materials (MSM) -- APR 30-MAY 03, 2015 -- Antalya, TURKEY
Keywords: Cooling Rate; at.Percent